The Role of Social Awareness in Growth and Development in Early Childhood - Mutmainnah Mutmainnah; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2023)
Social awareness of early childhood is the awareness and ability of a child to socialize or interact with other people in a social context in a certain way that is acceptable. Early childhood is also referred to as the golden age, because at that age, children's physical and motor abilities develop and grow very quickly. Children begin to be sensitive to receiving stimulation. Therefore, social awareness of early childhood must be optimally developed. This study aims to collect various references related to social awareness in early childhood. This research is a literacy study, where articles are obtained through the DOAJ (Directory of Open Access Journals) website, Academia Edu, Google Classroom, and ScienceDirect. The reference criteria used are references published between 2005-2022. Based on various references that have been collected, social awareness has an important role in the life of the child itself. This is because social awareness in early childhood can affect their further development.